Internet awareness and utilization as an information source at a Nigerian university (2008)
"This article examines the level of accessibility and the benefits derived from utilizing the Internet as an information source by final year undergraduate students of Ladoke Akintola University of Technology, Nigeria. A questionnaire was used to gather data from undergraduates students in the Faculties of Agriculture, Science, Technology Environmental Science. The results revealed that Nigerian undergraduate students appreciate and know the benefits of utilizing the facilities provided by the Internet for their academic pursuits. However, they are faced with problems such as exorbitant charges by commercial centers where they browse the Internet, erratic . power supply and poor telecommunication infrastructure. The study also discovered that the private sector computer business is really flourishing in Nigeria because most Nigerian Universities do not have internet facilities except the one provided by private organizations."